Effect of different ionic liquids on the dispersion and phase selective wetting of carbon nanotubes in rubber blends. (22nd November 2016) - Le, H.H.; Das, A.; Basak, S.; Tahir, M.; Wießner, S.; Fischer, D.; Reuter, Uta; Stöckelhuber, K.W.; Bhowmick, A.K.; Do, Q.K.; Heinrich, G.; Radusch, H.-J.
Abstract: The aim of this work was to study the effect of the ionic liquids (ILs) with respect to their anion type and the length of alkyl chain as dispersing and coupling agent in carbon nanotube (CNT) filled styrene butadiene rubber (SBR)/natural rubber (NR) blends. We characterized the ILs by their surface tensions whereupon their different values explain the different compatibilities of ILs with the rubber components and the filler. The wetting concept was further developed in order to experimentally characterize the effect of the rubber-IL and CNT-IL compatibility on the selective wetting of CNTs in rubber blends. It was found that all the used ILs improved the dispersion of CNTs in rubber blends significantly. During the mixing process the IL layer pre-bound to the CNT surface was replaced mainly by the NR phase and, partly, by the SBR phase. Thus, ILs cannot be used as coupling agent in this rubber blend. For the ILs with surface tension similar to that of CNTs the filler was partly wetted by IL that imparts the mixture a high electrical conductivity directly after the mixing process. This high conductivity can be used for triggering the vulcanization of the blend by means of the Joule heating. The preferential localization of ILs in the rubber matrix - but not in rubber-filler interphase - considerably influences the cross-link behavior of the vulcanizates and thus their final mechanical properties significantly. Graphical abstract: Highlights: Effect of the rubber-ionic liquid and filler-ionic liquid interaction on the CNT dispersion. Prediction and experimental determination of the selective wetting of CNTs in rubber blends. Replacement of pre-bound ionic liquid layer on the CNT surface mostly by NR and, partly by SBR. Improved network formation of CNTs partly wetted by IL. Joule heating triggered vulcanization of rubber blend by application of an electrical voltage.